Use of ultrasonic elastography in the differential diagnosis of pancreatic cystic lesions - T. V. Dibina; E. S. Drozdov; A. P. Koshel; V. R. Latypov (Бюллетень сибирской медицины)
Aim. Evaluate the effectiveness of ultrasonic elastography in the differential diagnosis of pancreatic cystic lesions.Materials and methods. Seventy patients with pancreatic cystic lesions were examined. Structure of clinical forms is the following: cystadenoma – 30 (serous cystadenoma – 23, mucinous cystadenoma – 2, mucinous cystadenocarcinoma – 5), pseudocysts – 40. Diagnosis of pancreatic cystic lesions was conducted with the help of transabdominal ultrasound examination (with 3D-reconstruction) and ultrasonic elastography.Results. The parameters of ultrasonic elastography for various types of pancreatic cystic lesions were determined. Sensitivity, specificity, positive predictive value, negative predictive value, the overall accuracy of the technique accounted for 97, 75, 74, 97 and 84% respectively. The superiority of the elastography technique over the standard transabdominal ultrasound in differential diagnosis of cystic pancreatic formations was illustrated.Conclusions. Ultrasonic elastography is an effective, non-invasive method of differential diagnosis of pancreatic cystic lesions and can be widely used in clinical practice.